2012
DOI: 10.1038/oby.2012.63
|View full text |Cite
|
Sign up to set email alerts
|

Rac1 Is a Possible Link Between Obesity and Oxidative Stress in Chinese Overweight Adolescents

Abstract: Enhanced nicotinamide adenine dinucleotide phosphate (NADPH) oxidase activity in the monocytes occurred in metabolic syndrome, hypertension, diabetes and obese patients in adults. However, whether NADPH oxidase is involved in the oxidative stress of overweight adolescents without comorbidities is still unclear. This study aimed to identify whether and how NADPH oxidase plays a crucial role in overweight adolescents. The study was performed in 93 overweight adolescents and 31 normal weight controls. Moreover, 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 24 publications
4
11
0
3
Order By: Relevance
“…As is shown in the current study, in addition to abnormal metabolic status, insulin resistance, and systemic oxidative stress in ob/ob mice, we also found that the ROS production and the expression of Rac1 were significantly increased in the pancreas of ob/ob mice. This result conforms with our former study that Rac1 might play a key role in obesity-related changes [9] and was further confirmed by the specific inhibition of Rac1. After 14 days administration of NSC23766, a specific activity inhibitor of Rac1, the serum levels of fasting glucose and the degree of insulin resistance declined along with the decrease of ROS production and Rac1 expression in pancreas, which suggested that the suppression of Rac1 could decline the oxidative stress level, ameliorate β cell function, and further improve glycometabolism.…”
Section: The Impairment Of β Cell Function Induced By Oxidative Stressupporting
confidence: 81%
See 2 more Smart Citations
“…As is shown in the current study, in addition to abnormal metabolic status, insulin resistance, and systemic oxidative stress in ob/ob mice, we also found that the ROS production and the expression of Rac1 were significantly increased in the pancreas of ob/ob mice. This result conforms with our former study that Rac1 might play a key role in obesity-related changes [9] and was further confirmed by the specific inhibition of Rac1. After 14 days administration of NSC23766, a specific activity inhibitor of Rac1, the serum levels of fasting glucose and the degree of insulin resistance declined along with the decrease of ROS production and Rac1 expression in pancreas, which suggested that the suppression of Rac1 could decline the oxidative stress level, ameliorate β cell function, and further improve glycometabolism.…”
Section: The Impairment Of β Cell Function Induced By Oxidative Stressupporting
confidence: 81%
“…caused by enhancing Rac1 expression and the augmented activity of NADPH oxidase [9]. In the present study, ob/ob mice displayed similar abnormal glucose and lipid metabolism and oxidative stress, which were highly consistent with our previous studies in overweight adolescents [14] and clinical studies that have indicated that obese patients are more susceptible to impaired glucose tolerance and an early-onset diabetes [15].…”
Section: The Impairment Of β Cell Function Induced By Oxidative Stressupporting
confidence: 81%
See 1 more Smart Citation
“…In support of our findings implicating sustained activation of Rac1 in islet b-cell in in vitro and in vivo models of glucolipotoxicity and T2DM are observations by Zhou and associates demonstrating significant increase in the expression and activation of Rac1 in pancreatic tissue from ob/ob mice, a model for obesity; these findings were replicated in insulinsecreting NIT-1b cells under hyper glycemic and hyper lipidemic conditions in vitro [43]. Recently, Sun et al [44] implicated Rac1 as key signaling protein to link obesity and NADPH oxidase derived oxidative stress in Chinese overweight adolescents. Sustained activation of Rac1-Nox2 signaling pathway has been reported in multiple cell types under various pathological conditions including cardiovascular diseases and diabetes [41,45,46].…”
Section: Which Implicates Protein Prenylation In Physiologicalsupporting
confidence: 84%
“…1. Increases in body mass index are associated with increases in circulating aldosterone levels [40], increases in tissue expression of 11β-HSD1 [23] and, in Chinese overweight adolescents, increases in the level of Rac1 expression in monocytes [41]. Weight loss is associated with decreases in aldosterone [42].…”
Section: Mr and The Cardiovascular And Renovascular Systems Inmentioning
confidence: 99%